Pretherapeutic (68)Ga-PSMA-617 PET may indicate the dosimetry of (177)Lu-PSMA-617 and (177)Lu-EB-PSMA-617 in main organs and tumor lesions - Wang, Jingnan (Clin Nucl Med, 2019)
AIM: Combined (68)Ga-PSMA-617 positron emission tomography (PET) imaging and (177)Lu-PSMA-617 therapy is a precise targeted theranostic approach for patients with metastatic castration-resistant prostate cancer (mCRPC). The purpose of this study was to determine whether pretherapeutic standard uptake value (SUV) in (68)Ga-PSMA-617 PET could indicate the effective dose in the main organs and absorbed dose in tumor lesions. METHODS: Following institutional review board approval and informed consent, 9 patients with mCRPC were recruited and underwent (68)Ga-PSMA-617 PET/computed tomography (CT) scans. Five patients received (177)Lu-PSMA-617 (1.30–1.42 GBq, 35–38.4 mCi) and then underwent serial whole-body planar imaging and single-photon emission computed tomography/CT (SPECT/CT) imaging of both thoracic and abdominal regions at 0.5, 2, 24, 48, and 72 h time points. The other 4 patients received (177)Lu-EB-PSMA-617 (0.80–1.1 GBq, 21.5–30 mCi) and then underwent the same imaging procedures at 2, 24, 72, 120, and 168 h time points. The effective dose in the main organs and the absorbed dose in tumor lesions were calculated. Detailed correlations between the pretherapeutic SUV in (68)Ga-PSMA-617 PET and effective dose in the main organs, as well as absorbed dose in the tumor lesions were analyzed. RESULTS: SUV of (68)Ga-PSMA-617 PET was moderately correlated with effective dose in main organs (r = 0.610 for (177)Lu-PSMA-617, r = 0.743 for (177)Lu-EB-PSMA-617, both P < 0.001). SUV of tumor lesions in (68)Ga-PSMA-617 PET had high correlation with those in (177)Lu-PSMA-617 (r = 0.915, P < 0.001) and moderate correlation with those in (177)Lu-EB-PSMA-617 (r = 0.611, P = 0.002). CONCLUSIONS: Pretherapeutic (68)Ga-PSMA-617 PET may indicate the dosimetry of (177)Lu-PSMA-617 and (177)Lu-EB-PSMA-617. Both the effective dose in main organs and absorbed dose in tumor lesions correlate with SUV of (68)Ga-PSMA-617 PET. This relationship may help select appropriate candidates for peptide receptor radionuclide therapy (PRRT). Further investigations of larger cohorts are needed to confirm these initial findings.